3D‐printed high‐gain circularly polarized antenna for broadband millimeter‐wave communications over the power line. Issue 3 (16th December 2019) - Zhang, Ziping; Lu, Yang; Liu, Guojun; Li, Jianqi; Song, Wei; Chen, Zhijiao
Abstract: It is well known that high transmission loss occurs when millimeter waves traveling through the atmosphere. As an alternative, power line is proposed as a transmission media to combat the high loss. In this article, a three‐dimensional (3D) printed high‐gain circularly polarized antenna was proposed for millimeter‐wave broadband power line communications. It has a simple structure, where tapered slots are designed between the upper and lower layers of the waveguide to generate the circularly polarized operation. A wide impedance bandwidth of 31.58% (24‐33 GHz) and an axial ratio bandwidth of 28.07% (24.5‐32.5 GHz) are achieved by the proposed design. A maximum gain of 11.2 dBi is measured from the 3D printed structure. The proposed antenna has a simple structure which is easy to adjust to any working frequency. The antenna can be excited by properly integrated to the waveguide that connected to the power line end. The use of 3D printing technology enables a low‐cost solution millimeter‐wave broadband communications over the power line.